Evaluation of preventive programs aimed at protecting children in the UAE: A qualitative study - Almarzooqi, Fatima; Algharaiba , Faker (Al-Adab Journal, 2025)
This research aims to analyze the content of preventive programs targeting children in the United Arab Emirates. It examines the preventive protection programs provided by governmental social institutions in the country, focusing on the areas of awareness these programs emphasize and the extent to which they incorporate methods to educate and empower children to protect themselves and report cases of violence. The study adopted a qualitative methodology, analyzing a sample of 23 child protection programs implemented by governmental social entities responsible for children in the UAE. The key findings indicate that preventive programs for children are delivered by various local social entities in Abu Dhabi, Dubai, and Sharjah, while some are managed at the federal level. These programs cover multiple areas of prevention, with a primary focus on raising children’s awareness of self-protection, followed by educating them about their rights under the UAE Child Protection Law (Wadeema Law), and emphasizing the importance of reporting abuse and using reporting hotlines specific to each emirate. The findings reveal that educating children on self-protection primarily involves raising awareness about avoiding compliance with strangers’ requests, which accounts for 22.3%. Programs aimed at educating children about their rights focus 16% on informing them about their right to protection from abuse. Regarding abuse reporting, 38% of programs focus on educating children about the free hotline numbers designated for reporting abuse in each emirate. Notably, despite the presence of multiple reporting hotlines across the UAE, all of them follow a unified plan for responding to reports and operate within an institutional network that enables case referrals based on the jurisdiction of each emirate.